Star Rainbow Coloring in Graphs - Jagannatharao, Kulkarni Sunita; Murali, R.; Jayashree, B. M. (Communications in Mathematics and Applications, 2023)
In this paper, we define a new coloring parameter called the star rainbow connection number of a connected graph \(G\), denoted by \(st_{rc}(G)\) and determine this parameter for some standard graphs.
Keywords: Rainbow connection number; Edge coloring; Rainbow path; Star rainbow connection number